To the question about diagnostics, prevention and therapy of pathology of the cervix - S O Dubrovina; O A Ardintseva; L V Krasilnikova; M V Varicheva; O A Afrikyan (IP Berlin A.V., 2018)
The review analyzes the latest American clinical guidelines on the effectiveness of cervical cancer screening programs, as well as references on the use of the immunomodulator isoprinosine for the treatment of patients infected with the human papilloma virus (HPV). The high prevalence of HPV and its role in the development of cervical cancer are shown. Isoprinosine belongs to immunomodulators with antiviral activity. It inhibits the replication of viral DNA and RNA by binding to cell ribosomes and changing their stereochemical structure. HPV infection, especially in the early stages, may be successfully cured till the complete elimination of the virus. Inosine Pranobex (Izoprinozin) having dual action and the most abundant evidence base, may be recognized as the optimal treatment option.